If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 7 = 3 + 4 Reorder the terms: 7 + X = 3 + 4 Combine like terms: 3 + 4 = 7 7 + X = 7 Add '-7' to each side of the equation. 7 + -7 + X = 7 + -7 Combine like terms: 7 + -7 = 0 0 + X = 7 + -7 X = 7 + -7 Combine like terms: 7 + -7 = 0 X = 0 Solving X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Simplifying X = 0
| 2x-7+4=11 | | 11x=77 | | X^2+14x+55=0 | | 4(-2)z+8(-2)+3+(-2)+6= | | 4x+3-2x=28 | | 18=6t | | 14-3x=47 | | -2x+-6+1=-7 | | 5-7x=-16 | | 5x+41=105-3x | | 4u^2-28u-72= | | 591x=3 | | -8x-2y=0 | | 0.5-(0.3x-0.6)=-1.5 | | y=-160-9(-9) | | -18+5x=-12+-1 | | x-8+x=2x-1 | | y=-160-9(x) | | -3x-2=3x-5+8 | | 4x^2-19x+35=2x+8 | | 5x=x+24 | | -2k+k-3k=7+2k-2 | | 3n-6(4n+5)=-3(n-2)-1 | | 15x+14-7x-28+8x+6-2x=0 | | -1=2(-1)+2 | | 5(2x-4)-2(7-x)=5x+1 | | 3x+2x-9+4x+17=180 | | 6(x-1)=12(x+2) | | 6x^2-7x+2=o | | 6(x+3)=7(x-3) | | -3(x-5)=(-3-4x) | | 4q=8q |